Gastroscopy as a rare cause of 'Slipped gastric band', in a patient with previous laparoscopic adjustable gastric band surgery. Issue 11 (17th November 2022) - Wilson, William; Zare, Benjamin
Abstract : A patient with a surgical history including an historic laparoscopic adjustable gastric band (LAGB) procedure presented to the emergency department with a history of haematemesis, intractable vomiting and abdominal pain 3 days following an outpatient oesophagogastroduodenoscopy (OGD) for chronic anaemia. A day after presentation to the emergency department, following admission, the patient underwent a repeat OGD. In contrast to her previous procedure, this demonstrated abnormal fluid and food deposition within what was originally reported to be a large hiatus hernia with a tight lower oesophageal sphincter. On corroboration with CT imaging obtained, in retrospect the endoscopic findings were attributed to slippage of the patient's adjustable gastric band. The band was loosened via its subcutaneous access port, following consultation with the surgical service, resulting in complete resolution of the patients' symptoms and she was discharged. This case is an example of gastroscopy as a rare trigger for the common complication of slipped gastric band following LAGB.